2011
DOI: 10.3945/jn.111.138180
|View full text |Cite
|
Sign up to set email alerts
|

Marginal Zinc Deficiency Exacerbates Experimental Colitis Induced by Dextran Sulfate Sodium in Rats

Abstract: We investigated the impact of Zn status on the maintenance of mucosal homeostasis. Rats were fed diets containing different amounts of Zn (30, 10, 5, <1 mg Zn/kg diet) for 21 d. Serum Zn concentrations were lower in rats fed marginally Zn-deficient (MZD; 5 mg Zn/kg diet) and severely Zn-deficient (<1 mg/kg) diets but not in those fed the marginally Zn-adequate diet (10 mg/kg) or the Zn-adequate (ZA; 30 mg/kg) group (P < 0.05). However, organ weights, colonic epithelial cell proliferation, and crypt fission did… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 43 publications
2
44
0
Order By: Relevance
“…We clearly demonstrated that LPS-stimulated leukocytes dramatically increased TNFα production in the ZD medium, but not in the ZA medium. The result corroborates those of a previous report showing that marginal Zn deficiency exacerbates experimental colitis (12). Additional studies (5, 10) have shown that Zn supplementation decreases LPS-, reactive oxygen species (ROS)-, or TNFα-induced nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) activation in endothelial and cancer cells.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…We clearly demonstrated that LPS-stimulated leukocytes dramatically increased TNFα production in the ZD medium, but not in the ZA medium. The result corroborates those of a previous report showing that marginal Zn deficiency exacerbates experimental colitis (12). Additional studies (5, 10) have shown that Zn supplementation decreases LPS-, reactive oxygen species (ROS)-, or TNFα-induced nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) activation in endothelial and cancer cells.…”
Section: Discussionsupporting
confidence: 82%
“…An increase in colonic MPO activity, a specific marker of PMN recruitment and activation, has been used as a measure of inflammatory status in experimental colitis (7). It has recently been reported that transepithelial resistance and lucifer yellow permeability in colonic tissues were maintained under marginal Zn deficiency (12). In this study, we did not Fig.…”
Section: Discussionmentioning
confidence: 33%
“…Ohkawara et al (205) demonstrated that polaprezinc (N-(3-Aminopropionyl)-Lhistidinato zinc), an anti-ulcer drug, suppresses DSS-induced colitis in mice, partly through inhibition of production of pro-inflammatory cytokines, suppression of neutrophils accumulation and cytoprotection by overexpression of heat shock proteins. This is consistent with Iwaya et al (207) whom reported that marginal zinc deficiency exacerbated colitis by modulating the immune response through the impairment of TNFα production and TNFR1 expression, rather than through the impairment of epithelial barrier function. Another potential mechanism of action of zinc in ulcerative colitis has been suggested by Luk et al (208) by reducing inflammation, inhibiting mast cell degranulation and histamine release.…”
Section: Animal Studiessupporting
confidence: 81%
“…To test the potential of our analysis in unraveling novel aspects of physiology in healthy and pathological conditions, as well as to link it with the underlying biological effects, we applied the ZNP network/functional analysis to a real case scenario. Zinc was shown to represent a key factor in maintaining the integrity of the intestinal epithelium, both in vitro and in vivo (Iwaya et al 2011;Sturniolo et al 2001Sturniolo et al , 2002. Several lines of evidence suggest that intestinal epithelial cells play a critical role in gut homeostasis in chronic inflammatory bowel disorders such as Crohn's disease (CD) and ulcerative colitis (UC).…”
Section: Topological Analysis Of the Znp Networkmentioning
confidence: 99%
“…Low levels of plasma zinc have frequently been associated with IBD, while zinc supplementation was reported to improve intestinal barrier function in CD patients, as well as in animal models, by contributing to the resolution of alterations in permeability of the gut mucosa and to reducing the risk of relapse (Hering and Schulzke 2009;Matsui 1998;Sturniolo et al 2001Sturniolo et al , 2002. Marginally, zinc-deficient diets were shown to worsen experimentally induced colitis in rats (Iwaya et al 2011), and in vitro evidences have shown that mild zinc deficiency renders intestinal cells susceptible to inflammatory cytokineinduced apoptosis, therefore contributing to epithelial barrier disruption (Ranaldi et al 2013).…”
Section: Introductionmentioning
confidence: 99%